Transformation of Religious Practice in the Digital Age: A Study of Virtual Ethnography of Online Spiritual Communities - Faza Achsan Baihaqi; Idaman idaman; Moh Safrudin (Journal of Law, Social Science and Management, 2025)
Background: The development of digital technology has brought significant changes across various aspects of life, including religious practices. The digital space has evolved not only as a medium of communication but also as a new spiritual arena, enabling individuals to perform and experience religious activities virtually. Objectives: This study aims to identify the forms of transformation in religious practices in the digital era and to understand the meaning of spiritual experiences within online religious communities. Methods: This research employs a qualitative approach using virtual ethnography. Data were collected through in-depth interviews with three active informants who participate in online spiritual communities via platforms such as YouTube, TikTok, and WhatsApp. Thematic analysis was conducted using an interview quote matrix. Results: The transformation of religious practices occurs across several dimensions, including initiation into digital communities, changes in forms of religious practice, shifts in religious perspectives, and the deepening of spiritual meaning. Furthermore, the study found that although interactions and solidarity within digital communities are limited, they are perceived as meaningful. The informants encountered technical challenges, while also recognizing opportunities such as easier access to spiritual resources and personal spiritual empowerment. Conclusion: Digital spiritual communities offer a new space for individuals to access and interpret religion in a flexible, participatory, and reflective manner. This phenomenon marks a significant shift in religious practice in the era of information technology.